2022
DOI: 10.1039/d1ta10385g
|View full text |Cite
|
Sign up to set email alerts
|

A robust eco-compatible microporous iron coordination polymer for CO2 capture

Abstract: Iron(III) carboxylate based Metal Organic Frameworks (MOFs) / porous coordination polymers (PCPs) have sparked a high interest owing to their high structural diversity and tunable porosity, excellent stability, tailored functionality...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…). 33–35 Firstly, the USPIO NPs were prepared using a coprecipitation method according to well-known procedures. 36,37 Their characterization by using PXRD, HRTEM, FT-IR spectroscopy, DLS and 57 Fe Mössbauer spectrometry has clearly shown the formation of maghemite ( i.e.…”
Section: Resultsmentioning
confidence: 99%
“…). 33–35 Firstly, the USPIO NPs were prepared using a coprecipitation method according to well-known procedures. 36,37 Their characterization by using PXRD, HRTEM, FT-IR spectroscopy, DLS and 57 Fe Mössbauer spectrometry has clearly shown the formation of maghemite ( i.e.…”
Section: Resultsmentioning
confidence: 99%
“…64 Our group has recently reported MMMs exhibiting a layered microstructure due to the preferential orientation of porous coordination polymer (PCP) platelets. 108 This PCP (labelled MIL-178(Fe)) exhibited interesting properties for CO 2 separation such as high hydrothermal stability, ultra-micropores and polar OH groups acting as CO 2 adsorption sites. 108 This material was synthesised as sub-micrometer-sized platelets through an easily-scalable and environmentally friendly protocol without using any toxic reactant.…”
Section: Nanostructuration and Hierarchy At The Morphology And Compos...mentioning
confidence: 99%
“…Such properties are likely due to the homogeneous dispersion and preferential orientation of MIL-178(Fe) llers in the polymer matrix, the absence of any interfacial defects, the increase of the CO 2 solubility and the lower crystallinity degree of the Pebax matrix in comparison to the pure polymer. 108 Alternatively, the control of the MOF nanocrystal morphology was achieved by using organic templates that not only guided the crystallisation of the MOF NPs but also imparted processability and mechanical properties to the composites. Such composites were oen prepared by the in situ synthetic approach in which the nucleation and growth of the MOF occurred in the presence of the organic template.…”
Section: Nanostructuration and Hierarchy At The Morphology And Compos...mentioning
confidence: 99%
“…Rodenas et al demonstrated that the preferential orientation of CuBDC nanosheets in CuBDC/PI MMMs would result in higher CO 2 /CH 4 separation performance and effective counteraction of undesired plasticizing effects under high pressure . Benzaqui et al revealed that the ordered stacking of MIL-178 platelets in the polymer matrix was beneficial for eliminating interfacial micro-void defects and therefore improving CO 2 /N 2 separation performance . In terms of UiO-66, the deliberate creation of missing linker/cluster defects opens up new opportunities in modulating the pore structure, catalytic activity, electronic property, adsorption, and separation ability. , For example, Biswas et al showed that using acetic acid as the modulator could promote the framework defect formation in UiO-66, thus significantly affecting its porosity, adsorption property, and hydrophilic–hydrophobic balance .…”
Section: Introductionmentioning
confidence: 99%